What Prompts Policy Change? Comparative Analyses of Efforts to Create Age-Friendly Cities in 14 Cities in Indonesia. Issue 3 (27th May 2019) - Suriastini, Wayan; Buffardi, Anne L.; Fauzan, Jejen
ABSTRACT: Four years after an age-friendly city (AFC) assessment across Indonesia, this article presents a comparative analysis of policy changes that have taken place across different AFC dimensions and factors associated with more and less change. Nine of fourteen cities initiated changes, ranging from public declarations, regulations, and creation or expansion of services. Our findings suggest that the AFC assessment can offer a means to engage policy makers, which in turn may facilitate city-level change, particularly for larger cities with more substantive budgets and more consolidated rather than dispersed leadership; however, no single factor represented a sufficient or necessary condition for change.